Optimizing the Prehospital-Hospital Emergency Care Path Application Value in Emergency Treatment of Patients with Cerebral Hemorrhage - Liu Lihui (Hindawi Limited, 2021)
Objective. To explore the effect of optimizing the prehospital-hospital emergency nursing path on the rescue speed, rescue effect, and patient prognosis of patients with cerebral hemorrhage. Methods. A retrospective study was performed to select 227 patients with acute cerebral hemorrhage who visited our hospital from August 2018 to October 2019, and we compared the optimization of the prehospital-hospital emergency nursing pathway (research group) with traditional prehospital time spent in the rescue and the prognosis of patients in the emergency care pathway (control group) in the hospital. The GOS score, FMA score, and Barthel index were used to compare the prognosis of the two groups of patients. Results. The prehospital-hospital emergency nursing route was optimized compared with the traditional nursing route. The rescue time of patients in each link was shorter (P<0.05), and the incidence of complications was low (P<0.05). The scales and scores all suggested that patients had a better prognosis (P<0.05). Conclusion. Optimizing the prehospital-hospital emergency nursing path can significantly shorten the rescue time, improve the rescue effect, and improve the prognosis of patients.